INTERACTION OF FASHION INDUSTRY AND INFORMATION TECHNOLOGY. DIGITAL AND PHYGITAL NEW FASHION TECHNOLOGY - X. H. Kamilova; X.M. Yunusxodjaeva; Z. Sobirova (Journals Park Publishing, 2022)
Today information teshnology is often used in the fashion industry to maintain competitiveness. There is a growing need to leverage IT, artificial intelligence teshnology and create innovations to take advantage among the fashion houses and meet consumer demand.